Analysis of the frequency of technical-tactical actions in taekwondo: a review (Revista de Artes Marciales Asiáticas, 2016)
Taekwondo (TKD) is a combat sport, focusing on head-height kicks, spinning kicks and skipping. The emphasis on technical-tactical combinations with speed and agility is an essential characteristic of this modality. Therefore, this review aims to contribute to the critical analysis of technical-tactical actions of TKD athletes, using relative effort and pause moments of official competitions. This review investigated tactical arrangements (i.e., attacks, defenses and blocks), technical performance (points), kicks and punches, regarding to weight category, age class and gender. In fact, rule changes in recent years have increased defensive actions in the senior category, with about 50% of actions in attacks, followed by 30% in defenses and 20% in blocking actions. While juniors tend to adopt an offensive strategy, with about 90% of the actions in attacks. Since the introduction of the scoring electronic system, high-performance athletes need to perform accurate and correct techniques to achieve scoring, so elite athletes have used short-distance techniques with kicks from the back leg. This action shows effectiveness in scoring and assists competitors in increasing defensive capability and counter-attacks. Consequently, training programs need to be specific to the rules, weight divisions, gender and age categories in elite athletes in TKD.